2015
DOI: 10.18378/rvads.v10i5.4268
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e desenvolvimento inicial da cultura da moringa (Moringa oleifera Lam.) submetida à fertilização orgânica

Abstract: <p>A moringa (<em>Moringa oleifera</em> Lam) é uma árvore nativa da Índia e de elevada importância principalmente pelo seu valor nutricional, medicinal e de purificação da água. Este trabalho teve como objetivo avaliar o efeito de níveis de fertilização orgânica no crescimento e desenvolvimento inicial de mudas de moringa nas condições semiáridas do Estado da Paraíba, Brasil. O experimento foi conduzido em condições de túnel plástico, localizado no Centro de Ciências e Tecnologia Agroalimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 3 publications
0
4
0
12
Order By: Relevance
“…It is common to increase the root dry matter mass during the course of the experiment, except when the plant undergoes some stress. Souza et al (2015) found positive results for increasing the dry matter mass of the M. oleifera root. However, Cavalcante et al (2016), evaluating doses of bovine litter in the production of Gliricidia sepium (Jacq.)…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…It is common to increase the root dry matter mass during the course of the experiment, except when the plant undergoes some stress. Souza et al (2015) found positive results for increasing the dry matter mass of the M. oleifera root. However, Cavalcante et al (2016), evaluating doses of bovine litter in the production of Gliricidia sepium (Jacq.)…”
Section: Resultsmentioning
confidence: 92%
“…This effect on the root dry matter mass, as a function of the doses, probably caused root toxicity, due to the excess of nutrients with increasing doses up to 120 g dm -3 , causing them to decrease the dry matter mass as a function of the increased poultry litter dose applied. Souza et al (2015) point out that large quantities of fertilizer are not necessary for M. oleifera plants to express a significant production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No diâmetro do coleto da moringa os resultados foram não significativos ao nível de 5% de probabilidade em função das doses de esterco ovino (Tabela 1). Enquanto, Souza et al (2015) estudando o crescimento e desenvolvimento da moringa em diferentes doses de esterco bovino estimaram um modelo quadrático para o diâmetro do colmo, tendo o coeficiente de determinação de 81,41 %. Medeiros et al (2017) descrevem o crescimento do diâmetro caulinar com aumento da dose de esterco bovino de modo satisfatório.…”
Section: Resultsunclassified
“…A produção de mudas de moringa em diferentes substratos foi estudada por Neves et al (2010) e Rodrigues et al, (2016). A adubação considerando diferentes fonte orgânicas na produção de mudas de moringa, esterco bovino, (SOUZA et al 2015), a cama de frango por Souza et al (2018), substrato comercial (ROSA et al (2018). Nesse contexto, o objetivo desse trabalho foi produzir mudas de moringa sob diferentes doses de esterco ovino e acompanhar o desenvolvimento das plantas.…”
Section: Introductionunclassified